1991
DOI: 10.2136/sssaj1991.03615995005500010026x
|View full text |Cite
|
Sign up to set email alerts
|

Acidification Induced by Different Nitrogen Sources in Columns of Selected Tropical Soils

Abstract: Sustainability in agriculture is a rising concern in the tropics where fertilizers are introduced to meet increasing food demands. The adverse effects of long‐term fertilizer use were monitored through changes in the soil exchange complex in packed columns of an Oxic Paleustalf, a Typic Paleudult, and a Tropeptic Haplustox. Following each application of N at rates of 0, 50, or 100 kg ha−1 as urea, ammonium sulfate (AS), or calcium ammonium nitrate (CAN), the soils were flushed with distilled water, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The decline in exchangeable Ca was less pronounced than that reported by other workers (Juo and Lal, 1977;Pieri, 1989;Raney, 1960;Stumpe and Vlek, 1991). This may be attributed to lower leaching losses under a subhumid climate, the recycling of plant nutrients with the return of crop residues after harvest, and/or to the no tillage system used.…”
Section: " -mentioning
confidence: 57%
See 2 more Smart Citations
“…The decline in exchangeable Ca was less pronounced than that reported by other workers (Juo and Lal, 1977;Pieri, 1989;Raney, 1960;Stumpe and Vlek, 1991). This may be attributed to lower leaching losses under a subhumid climate, the recycling of plant nutrients with the return of crop residues after harvest, and/or to the no tillage system used.…”
Section: " -mentioning
confidence: 57%
“…Differences in the rate of soil acidification with the three N sources are based on their potential acidification, which is twice that of urea for AS, and 85% that of urea for CAN (Stumpe and Vlek, 1991). Greater soil acidification with AS than with UA or CAN was previously found under field conditions by Brochado-Miranda (1976), Fox and Hoffman (1981), Jones (1976) and Khonje et al (1989) and under laboratory conditions by Stumpe and Vlek (1991). The ).…”
Section: " -mentioning
confidence: 81%
See 1 more Smart Citation
“…8,9,10,11 and 12). The reason for slope values of less than 1 can be attributed to the protons being neutralized either by cation exchange or through plant uptake (Stumpe and Vlek 1991;Bolan et al 1991). While for the G12 soil, there must be other proton sources in addition to nitrification, which led to the higher slope of the line.…”
Section: Change In Soil Acidity and Salinitymentioning
confidence: 99%
“…In general, N fertilizers affect soil acidity because of the preferential uptake of nitrate-N to bases by most crops and the excretion of hydroxide ions to balance the charge reduces acidity (Jolley & Pierre 1977, Pierre et al 1971. Juo et al (1995aJuo et al ( , 1995bJuo et al ( , 1996 reported soil acidification followed by a considerable decline of exchangeable Ca in the topsoil horizons of the Egbeda series under continuous maize-based systems, which would arise from nutrient removal by crop harvest (Jaiyeoba 1995, Sharma et al 2009), application of ammoniacal fertilizers and nitrification of applied N (Stumpe & Vlek 1991). In this study, the application of triple super phosphate containing Ca (12%, w/w) may have helped to replenish the exchangeable Ca and prevent acidification in the soil of the cropland.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%